Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

As above, let
$f(x) = 3\cdot\frac{x^4+x^3+x^2+1}{x^2+x-2}.$Give a polynomial $g(x)$ so that $f(x) + g(x)$ has a horizontal asymptote of $y=0$ as $x$ approaches positive infinity.


As Above Let Fx 3cdotfracx4x3x21x2x2Give A Polynomial Gx So That Fx Gx Has A Horizontal Asymptote Of Y0 As X Approaches Positive Infinity class=

Sagot :

caylus

Answer:

Hello,

Step-by-step explanation:

[tex]\dfrac{f(x)}{3} =\dfrac{x^4+x^3+x^2+1}{(x-1)(x+2)} \\\\=\dfrac{(x^2+3)(x-1)(x+2)-3x+7}{(x-1)(x+2)} \\=x^2+3-\dfrac{3x-7}{(x-1)(x+2)} \\\\=x^2+3-\dfrac{3}{x-1} +\dfrac{1}{(x-1)(x-2)} \\\\\dfrac{f(x)}{3}-\dfrac{3x^2+9}{3} =-\dfrac{3}{x-1} +\dfrac{1}{(x-1)(x-2)} \\\\\\ \lim_{x \to +\infty} (\dfrac{f(x)}{3}-\dfrac{3x^2+9}{3} )\\\\=0+0=0\\\\\\P(x)=-x^2-3[/tex]

Answer:

[tex]g(x)=-3x^2-9[/tex]

Explanation:

[tex]3\frac{x^4+x^3+x^2+1}{x^2+x-2}[/tex]

+[tex]\frac{p(x)(x^2+x-2)}{x^2+x-2}[/tex]

We need p(x) need to be a degree 2 polynomial so the numerator of the second fraction is degree 4. Our goal is to cancel the terms of the first fraction's numerator that are of degree 2 or higher.

So let p(x)=ax^2+bx+c.

[tex]3\frac{x^4+x^3+x^2+1}{x^2+x-2}[/tex]

+[tex]\frac{p(x)(x^2+x-2)}{x^2+x-2}[/tex]

Plug in our p:

[tex]3\frac{x^4+x^3+x^2+1}{x^2+x-2}[/tex]

+[tex]\frac{(ax^2+bx+c)(x^2+x-2)}{x^2+x-2}[/tex]

Take a break to multiply the factors of our second fraction's numerator.

Multiply:

[tex](ax^2+bx+c)(x^2+x-2)[/tex]

=[tex]ax^4+ax^3-2ax^2[/tex]

+[tex]bx^3+bx^2-2bx[/tex]

+[tex]cx^2+cx-2c[/tex]

=[tex]ax^4+(a+b)x^3+(-2a+b+c)x^2+(-2b+c)-2c[/tex]

Let's go back to the problem:

[tex]3\frac{x^4+x^3+x^2+1}{x^2+x-2}[/tex]

+[tex]\frac{ax^4+(a+b)x^3+(-2a+b+c)x^2+(-2b+c)x-2c}{x^2+x-2}[/tex]

Let's distribute that 3:

[tex]\frac{3x^4+3x^3+2x^2+3}{x^2+x-2}[/tex]

+[tex]\frac{ax^4+(a+b)x^3+(-2a+b+c)x^2+(-2b+c)x-2c}{x^2+x-2}[/tex

So this forces [tex]a=-3[/tex].

Next we have [tex]a+b=-3[/tex]. Based on previous statement this forces [tex]b=0[/tex].

Next we have [tex]-2a+b+c=-3[/tex]. With [tex]b=0[/tex] and [tex]a=-3[/tex], this gives [tex]6+0+c=-3[/tex].

So [tex]c=-9[tex].

Next we have the x term which we don't care about zeroing out, but we have [tex]-2b+c[/tex] which equals [tex]-2(0)+-9=-9[/tex].

Lastly, [tex]-2c=-2(-9)=18[/tex].

This makes [tex]p(x)=-3x^2-9[/tex].

This implies [tex]g(x)\frac{(-3x^2-9)(x^2+x-2)}{x^2+x-2}[/tex] or simplified [tex]g(x)=-3x^2-9[/tex]

Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.